Safety and Tolerability of Insulin Aspart Biosimilar SAR341402 Versus Originator Insulin Aspart (NovoLog) When Used in Insulin Pumps in Adults with Type 1 Diabetes: A Randomized, Open-Label Clinical Trial - Thrasher, James (Diabetes Technol Ther, 2020)
Background: The aim was to assess the safety and tolerability of the insulin aspart biosimilar/follow-on product SAR341402 (100 U/mL solution; SAR-Asp) and originator insulin aspart (100 U/mL; NN-Asp; NovoLog(®)) self-administered through an insulin pump. Materials and Methods: This randomized, open-label, 2 × 4-week crossover study enrolled 45 adults with type 1 diabetes (T1D). Participants were randomized 1:1 to the treatment sequence SAR-Asp/NN-Asp or NN-Asp/SAR-Asp. The basal and prandial insulin doses were individually titrated. The primary outcome was the number of participants with at least one infusion set occlusion (infusion set change due to failure-to-correct hyperglycemia [plasma glucose ≥250 mg/dL] by insulin pump bolus) during the 4-week treatment. The main secondary outcome was the number of participants with at least one episode of unexplained hyperglycemia (regardless of correction by an insulin pump bolus without apparent material defect, medical, dietary, insulin dosing reason, or pump problem). Results: The number of participants reporting ≥1 infusion set occlusion were similar between treatments: 14/43 on SAR-Asp (33 events) and 12/43 on NN-Asp (24 events). The estimated difference in infusion set occlusion risk for SAR-Asp versus NN-Asp was 4.1% (95% confidence interval: −9.3% to 17.4%). The number of participants with ≥1 episode of unexplained hyperglycemia was similar between treatments (31/43 on SAR-Asp [154 events]; 32/43 on NN-Asp [175 events]). Hypoglycemia, treatment-emergent adverse events, hypersensitivity, and injection site reactions were similar between treatments. Conclusions: SAR-Asp and NN-Asp were well tolerated and had similar infusion set occlusions over a 4-week period in insulin pump users with T1D.